RELATIONSHIP BETWEEN CONTINUOUS IMPROVEMENT AND QUALITY CYBERSECURITY - Aseel Ali Mezher; Amir Sajit Mdlool (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Current research aims to highlight the impact of continuous improvement in cybersecurity quality. The research adopted the identification as a basic measurement tool for collecting data from the sample in question, which amounted to 141 of the 150 affiliates of the cybersecurity department of the Iraqi National Security Service, where it was employed to test the main and subsidiary research hypotheses through the use of a number of statistical means, most notably (SPSS vr. 20, AMOS vr. 20) The results of the research have proved the most valid hypotheses, and the research has reached a set of conclusions, most notably that there is a role for continuous improvements in the work of the National Security Service/Cyber Security Department.